Interactions between Ultraviolet Light and MC1R and OCA2 Variants Are Determinants of Childhood Nevus and Freckle Phenotypes - Barón, Anna E.; Asdigian, Nancy L.; Gonzalez, Victoria; Aalborg, Jenny; Terzian, Tamara; Stiegmann, Regan A.; Torchia, Enrique C.; Berwick, Marianne; Dellavalle, Robert P.; Morelli, Joseph G.; Mokrohisky, Stefan T.; Crane, Lori A.; et al. (Cancer epidemiology, biomarkers & prevention, 2014)
Background: Melanocytic nevi (moles) and freckles are well known biomarkers of melanoma risk, and they are influenced by similar UV light exposures and genetic susceptibilities to those that increase melanoma risk. Nevertheless, the selective interactions between UV exposures and nevus and freckling genes remain largely undescribed. Methods: We conducted a longitudinal study from ages 6 through 10 years in 477 Colorado children who had annual information collected for sun exposure, sun protection behaviors, and full body skin exams. MC1R and HERC2/OCA2 rs12913832 were genotyped and linear mixed models were used to identify main and interaction effects. Results: All measures of sun exposure (chronic, sunburns, and waterside vacations) contributed to total nevus counts, and cumulative chronic exposure acted as the major driver of nevus development. Waterside vacations strongly increased total nevus counts in children with rs12913832 blue eye color alleles and facial freckling scores in those with MC1R red hair color variants. Sunburns increased the numbers of larger nevi (≥2 mm) in subjects with certain MC1R and rs12913832 genotypes. Conclusions: Complex interactions between different UV exposure profiles and genotype combinations determine nevus numbers and size, and the degree of facial freckling. Impact: Our findings emphasize the importance of implementing sun-protective behavior in childhood regardless of genetic make-up, although children with particular genetic variants may benefit from specifically targeted preventive measures to counteract their inherent risk of melanoma. Moreover, we demonstrate, for the first time, that longitudinal studies are a highly powered tool to uncover new gene–environment interactions that increase cancer risk. Cancer Epidemiol Biomarkers Prev; 23(12); 2829–39. ©2014 AACR.